Evolution of microstructure and mechanical properties of Mg–3.0Zn–0.2Ca–0.5Y alloy by extrusion at various temperatures - Sun, Hong-fei; Li, Cheng-jie; Fang, Wen-bin (Journal of materials processing technology, 2016)
In the current study, the effects of extrusion temperatures on the extrudability, microstructure, recrystallization behavior and mechanical properties of the Mg–3.0Zn–0.2Ca–0.5Y alloy have been systematically investigated. The results show that the magnesium alloy bars with excellent mechanical properties are obtained at the extrusion temperature above 523K. Both the dynamic recrystallized grain size and fraction increase with an increase in the deformation temperature. The MgY phase particles (>1μm) contribute to increasing DRX fraction, while the finer I-phase precipitates exert a pinning effect on the movement of grain boundaries and thus suppress the grain growth. The competitive mechanism between the particle-stimulated nucleation and grain boundary pinning determines the final microstructure that strongly affects the mechanical properties of the extruded alloys. The yield strength is improved with the decrease of the DRX grain size by grain boundary strengthening, and the ductility is increased by the enhanced work hardening ability with the increase of the DRX fraction.